The impact of knowledge management strategies on tax compliance. An applied study in the General Tax Authority - Haider Mutasher Al-Kaabi (Technium Business and Management, 2024)
The compliance decision is merely a moral decision made by the taxpayer about what to report as taxable income. as the economies of knowledge-based societies have extended their shadows over all areas of both public and private sectors, the study of the effects of knowledge management strategies on the study of tax compliance can be considered a cognitive addition and a new field of study. The current study aims to examine the relationship between knowledge management strategies in enhancing tax compliance with the tax authority in the country of Iraq. After conducting the research, the second conclusion is the choice of a questionnaire tool as the measuring tool of the research along with the extrapolation of previous research efforts and benefits from other countries. A 12-Question Survey Was Sent To 62 Tax assessors and auditors working in the Ministry of Finance/General Tax are instrumental in this process. The notable impact of knowledge management strategies is attributable to the interconnectedness and significance of these strategies, both in specific contexts and within the overarching domain of knowledge management. These strategies are derived from and exert a substantial influence on tax compliance, which in turn exerts a notable effect on accounting systems in general. Consequently, knowledge management strategies, and tax education in particular, directly impact the development of tax compliance and the reduction of tax evasion at the state level.This research in the field of social impact is expected to open new horizons for managers in tax administration by organizing their knowledge management strategies and making them keep pace with the development of change and improvement. This contributes to upgrading tax compliance, which leads to maximizing the state’s paramount financial assets.